Vacuolated PAS-Positive Lymphocytes on Blood Smear: An Easy Screening Tool and a Possible Biomarker for Monitoring Therapeutic Responses in Late Onset Pompe Disease (LOPD) - Parisi, Daniela; Musumeci, Olimpia; Mondello, Stefania; Brizzi, Teresa; Oteri, Rosaria; Migliorato, Alba; Ciranni, Annamaria; Mongini, Tiziana E.; Rodolico, Carmelo; Vita, Giuseppe; Toscano, Antonio (Frontiers in Neurology, 2018)
Background: Primary aim was to investigate the diagnostic value of PAS-positive vacuolated lymphocytes on blood smear in Late Onset Pompe Disease (LOPD) patients and, secondly, to evaluate its potential utility in monitoring treatment effects. Methods: We examined blood smear of 26 LOPD patients. We evaluated 10 treated and 16 untreated LOPD patients. Among the latter group, 7 patients later initiated ERT and were tested again 6 months after start. Blood smear was also sampled from 82 controls and 19 patients with other muscle glycogenoses (MGSDs). PAS staining was used to evaluate: 1) presence of lymphocytes with glycogen-filled vacuoles, 2) quantification of vacuolated lymphocytes. Results: We found that PAS-positive lymphocytes were significantly higher in LOPD patients than in controls or other MGSDs (p<0.05 and p<0.001, respectively). ROC curve for discriminating between untreated LOPD patients and controls yielded an AUC of 1.00 (95%CI 1.00-1.00; P<0.0001). PAS-positive lymphocyte cutoff level of >10 yielded sensitivity of 100% (95%CI 78%-100%), specificity of 100% (95%CI 96%-100%), and positive predictive value of 100%. Patients studied before and after ERT showed a dramatic decrease of PAS-positive vacuolated lymphocytes number (p=0.016). In other MGSDs, PAS-positive lymphocytes were significantly lower that untreated LOPD patients but higher than controls. Conclusions: Our data suggest that the Blood Smear Examination (BSE) for PAS-positive lymphocytes quantification could be used as a simple and sensitive test for a quick screening of suspected Pompe disease. The quantification of vacuolated lymphocytes appears to be also a valuable tool for monitoring the efficacy of treatment in LOPD patients.